2020
DOI: 10.3390/jcm9040930
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Immunity in Renal Carcinoma: Can We Turn an Unhappy Relationship into a Happy Marriage?

Abstract: The frontline treatment options for patients with metastatic renal cell carcinoma (mRCC) are evolving rapidly since the approval of combination immunotherapies by the U.S. Food and Drug Administration (USFDA) and the European Medicines Agency (EMA). In particular, in combination with vascular endothelial growth factor receptor (VEGFR) tyrosine-kinase inhibitors (TKIs), immune checkpoint inhibitors (ICIs) have significantly improved the outcome of patients with mRCC compared to TKI monotherapy. Here, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 88 publications
1
27
0
Order By: Relevance
“…Regarding the combination of ICI plus sunitinib, although the authors comprehensively demonstrated a direct impact of immune-and inflamed-infiltration (Teff High Myeloid High ) [73], it is still debated whether combining anti-angiogenic and immunological checkpoint inhibitors without proper selection, more than what would necessary constitutes a synergistic strategy [104]. Nonetheless, robust and compelling preclinical [20,104] and clinical [18] evidence supports the biological ecosystem dissection as the future driver of patient selection for choosing candidates among ICI/anti-angiogenic strategies: different biological RCC behaviors pinpoints the tight correlation existing by intermediate/high risk profile, tumor angiogenesis and indirect immune-tolerogenic milieu. Statistically powered prospective clinical studies are expected to be carried out, aiming at further validating the promising pioneering results [105].…”
Section: Therapeutic Window Driven By Angiogenesis and The Immune Sysmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the combination of ICI plus sunitinib, although the authors comprehensively demonstrated a direct impact of immune-and inflamed-infiltration (Teff High Myeloid High ) [73], it is still debated whether combining anti-angiogenic and immunological checkpoint inhibitors without proper selection, more than what would necessary constitutes a synergistic strategy [104]. Nonetheless, robust and compelling preclinical [20,104] and clinical [18] evidence supports the biological ecosystem dissection as the future driver of patient selection for choosing candidates among ICI/anti-angiogenic strategies: different biological RCC behaviors pinpoints the tight correlation existing by intermediate/high risk profile, tumor angiogenesis and indirect immune-tolerogenic milieu. Statistically powered prospective clinical studies are expected to be carried out, aiming at further validating the promising pioneering results [105].…”
Section: Therapeutic Window Driven By Angiogenesis and The Immune Sysmentioning
confidence: 99%
“…From this perspective, the phenotypic deconvolution aiming to biomarkers identification and response prediction, can support customizing RCC treatment. From this standpoint, it is tempting to propose a combination of anti-angiogenic and immune-checkpoint inhibitors (ICI), especially when driven by compelling molecular signatures [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…with x i expressed in mg/(mL•day). When combined with antiangiogenesis, immunotherapy increases the therapeutic effect with 25% [1,16,17,45] and up to 50% when combined with radiotherapy [15,34,35,46]. A linear combination of their synergic effect is considered for the tumor Et all and drug Ed all interactions:…”
Section: Proposed Combined Therapy Minimal Modelmentioning
confidence: 99%
“…It has been shown that combination therapy in cancer leads to synergic effects with improved outcome [ 1 , 2 ]. The SBRT (stereotactic body radiotherapy) is prevalent in lung cancer treatment as it is most patient friendly in terms of side effects, while proving to have excellent results [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TME is, in fact, a complex structure composed of different mediators involved in the cell signaling that may deeply influence sensitivity to immunotherapy. 26 In particular, the inactivation of VHL tumor suppressor gene, present in about 60% of RCC, results in an imbalance in pro-and anti-angiogenic factors. 27 Among the proangiogenic factors involved, the transcription factor hypoxia-inducible factor (HIF)-1α and VEGF induce the release of immunosuppressive factors, such as transforming growth factor β (TGF-β), PD-L1, and VEGF itself.…”
Section: Anti-pd-1 Agentsmentioning
confidence: 99%